(untitled) (International Journal of Design (INJUDES), 2021)
The attractive appearance of the system applications on the Android phone is quite important. There is an initial premise that the "Imaji Library" application that the Selasar Imaji Library owns is less attractive to users because it is not attractive. This study aims to explore an attractive appearance based on studies that are filtered to application users. Through Research and Development (R&D) activities, by 1) capturing questionnaire results from users to find out what is less attractive from the application display; 2) study of the search for the preferred visual appearance; 3) designing applications; and 4) application testing to librarians. The results of the exploration activities are in the form of (1) a new prototype design of the "Imaji Library" application display, (2) the development of application features in terms of procurement, processing, tracking, and member and circulation management activities. The implication of this research is helpful for librarians’ convenience in managing libraries.